2016
DOI: 10.1016/j.ocemod.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling surface currents in the Eastern Levantine Mediterranean using surface drifters and satellite altimetry

Abstract: International audienceWe present a new and fast method for blending altimetry and surface drifters data in the Eastern Levantine Mediterranean. The method is based on a vari-ational assimilation approach for which the velocity is corrected by matching real drifters positions with those predicted by a simple advection model, while taking into account the wind effect. The velocity correction is done in a time-continuous fashion by assimilating at once a whole trajectory of drifters using a sliding time window. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Variational methods that take into account the temporal variation within the optimization are called 4D-Var (Kamachi and O'Brien, 1995;Mead, 2005;Nodet, 2006;Carrier et al, 2014;Muscarella et al, 2015). A more detailed review of various assimilation methodologies can be found in Issa et al (2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Variational methods that take into account the temporal variation within the optimization are called 4D-Var (Kamachi and O'Brien, 1995;Mead, 2005;Nodet, 2006;Carrier et al, 2014;Muscarella et al, 2015). A more detailed review of various assimilation methodologies can be found in Issa et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…From the application point of view, merging altimetry and in-situ data for a better estimation of the sea surface circulation has previously had several successful applications: for example in the Gulf of Mexico (Carrier et al, 2014;Muscarella et al, 2015;Berta et al, 2015), the Black Sea (Kubryakov and Stanichny, 2011;Stanichny et al, 2016), the North Pacific (Uchida and Imawaki, 2003), and the Mediterranean Sea (Taillandier et al, 2006;Menna et al, 2012;Issa et al, 2016), each of them using different methodologies for merging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, altimetry-derived velocities are geostrophic and represent only a part, also very important, of the current velocity [31]. Wind-driven currents are another important part of the surface currents, and should be additionally described using different assumptions [32][33][34][35] to reconstruct total surface currents on the basis of satellite altimetry. Such an approach was used, for example, to simulate drift trajectories or oil spill propagation [34,36], and it was shown that it may perform better than the data assimilative models in [36].…”
Section: Introductionmentioning
confidence: 99%